Gestão social de bens comuns urbanos no contexto da cidade justa, democrática e sustentável: o caso da orla do Portal da Amazônia, em Belém (PA) - ALBUQUERQUE, Maria Claudia Bentes (Universidade Federal do Pará, 2018)
The concepts of fair, democratic and sustainable city started to be drawn in the 1970s, from international events discussing urban sustainability. These concepts changed the way of thinking about the cities ownership and management. Brazil has incorporated the concept of type of cities in its legal system in the Constitution of 1988 and in the City Statute. Given this context, this research was guided by the following question: How is the management of common goods implemented taking into account the existence of a theoretical, legal and institutional foundation of fair, democratic and sustainable city? To understand how to operationalize such city model, this study also uses other elements extracted from the theories of Commons Resources Management from Ostrom (2011) and Social Management from Cançado, Pereira and Tenório (2015) from the case of the Portal da Amazônia waterfront, Belém (PA). The overall objective of the research was to analyze what the common goods management in urban areas is like, considering two theoretical frameworks: the fair, democratic and sustainable city concept and the theoretical precepts of Social Management. The research revealed that the variables participation and cooperation are points of convergence between the two theoretical frameworks used in this study. This result demonstrates the possibility to apply social management models for urban common goods. The research methodology is qualitative with analytical-descriptive and exploratory approaches. The chosen research method was the single case study. The empirical research has demonstrated that none of the applied criteria to evaluate participation and cooperation in the unit of analysis was in accordance with the theoretical models applied in the study. Data collected by documentary sources and interviews indicated distance between the theory and the observed reality, as well as insufficient initiative in the management of urban space, demonstrating that the concept of fair, democratic and sustainable city is not a reality in Belém yet. A conclusion from this analysis is that the current urban-environmental problems faced by the municipality derive from the process of formation of the city and its waterfronts. In addition, legislative weaknesses, inadequate theoretical and political conceptions of planning and of common urban resources management are contributing to increase private appropriation of public spaces that should be directed for collective use, hampering free access, ownership, usufruct and common resource management by the community.